Modeling and Analysis of the Kinetic Influence of Liquid Sloshing Characteristics on High-Clearance Sprayers. (12th November 2021) - Wang, Weijun; Feng, Jing'an; Wan, Wenkang; Zhang, Peng; Yang, Songlin
Abstract : To research the influence of liquid sloshing on the driving stability of high-clearance sprayers, this paper builds an equivalent liquid sloshing mechanical model and obtains the stochastic acceleration excitation of the rectangular spray tank using the Adams kinetic model, thus obtaining the relationship between the impact force, moment, and the stochastic acceleration using Fluent numerical simulation analysis. This paper makes further calculations with MATLAB/Simulink system models, and the result from comparing these two calculations shows that the equivalent strategy proposed in this paper has a better consistency. Based on the consideration of the acting forces of the additional moment due to lateral movement of the center of mass of the liquid and the dynamic pressure due to liquid sloshing in the tank, this paper builds a mathematical model of the sprayer and researches the influence of the filling ratio and vehicle velocity on the vehicle stability through stochastic acceleration excitation. The results show that, in the case of different speeds, the liquid sloshing has a small influence on the overall roll angle; in the case of different filling ratios, the liquid sloshing has a big influence on the overall roll angle, the slip angle of the center of mass, and the yaw angular velocity; the filling ratio k = 0.85 and the speed u = 1 m/s −2 m/s are safe operation parameters of the sprayer. This research provides reference solutions for the stability control and optimization problems of the high-clearance sprayer and semitrailer.